Instructional Leadership, Differentiated Instruction, Community of Practice, and Student Wellbeing: Based on the Perspective of the Principal Strengthening Training Policy - Riyadi, Aris; Bafadal, Ibrahim; Burhanuddin, Burhanuddin; Timan, Agus (Pedagogika, 2023)
This study aimed to examine the relationship between the principal’s instructional leadership, differentiated instruction, community of practice, and student wellbeing. This study uses multiple regression analysis with the consistent PLS. The results showed that instructional leadership has a positive relationship with differentiated instruction and a community of practice. Differentiated instruction and community of practice have a positive relationship with student wellbeing.